1987
DOI: 10.1128/jcm.25.12.2314-2316.1987
|View full text |Cite
|
Sign up to set email alerts
|

Large production of cholera toxin by Vibrio cholerae O1 in yeast extract peptone water

Abstract: A large amount of cholera toxin (CT) was produced by Vibrio cholerae 01 cultured in yeast extract-peptone water. The organisms were cultured initially in a stationary test tube (small surface-to-volume ratio) until the end of the exponential phase and subsequently cultured in a shaking flask for 15 to 20 h. By this method (previously reported as the AKI-SW method), most cholera vibrios produced an abundance of CT (up to 64 ,ig/ml), regardless of their biotype and serotype. A substantial amount of CT was produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…Transient transcription apparently takes place in response to the combination of static growth and culture cell density because induction occurred during the static period and at the early stationary phase. These results are in agreement with the initial physiological studies performed by Iwanaga et al, who showed that a 4-h static growth period followed by strong aeration was optimal to stimulate CT production in V. cholerae El Tor (17,18). We found that ToxR-driven transcription of toxT was initiated precisely at the h 4 yet expression was transient, continuing for only 1 h during shaking.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Transient transcription apparently takes place in response to the combination of static growth and culture cell density because induction occurred during the static period and at the early stationary phase. These results are in agreement with the initial physiological studies performed by Iwanaga et al, who showed that a 4-h static growth period followed by strong aeration was optimal to stimulate CT production in V. cholerae El Tor (17,18). We found that ToxR-driven transcription of toxT was initiated precisely at the h 4 yet expression was transient, continuing for only 1 h during shaking.…”
Section: Discussionsupporting
confidence: 93%
“…Strains were maintained at Ϫ70°C in LB medium containing 20% glycerol. The classical V. cholerae strain O395 was grown at 30°C in LB medium, and the V. cholerae El Tor strain E7946 was grown at 37°C in AKI medium (17) without sodium bicarbonate (18). The classical strain was used to generate a toxT primer extension product used as a reference to estimate the sizes of the toxT and ctxA primer extension products from the El Tor strain.…”
Section: Methodsmentioning
confidence: 99%
“…From the evaluation study, it was demonstrated that the bead-ELISA was more sensitive than the RPLA for detection of CT from broth cultures of strains of V. cholerae O1. It has been reported that the cultural requirements for optimal production of CT by V. cholerae O1 vary between classical and eltor biotype (4,12,13), and among strains even in the same biotype (unpublished observation). In This work was supported in part by a Grant-in-Aid for Scientific Research from the Ministry of Education, Science and Culture of Japan.…”
Section: Discussionmentioning
confidence: 96%
“…Biochemical behaviors were examined in accordance with the routine laboratory methods used to identify V cholerae. Cholera toxin production was examined in YEP medium under AKI-SW conditions and was determined by the reversed passive latex agglutination method (2 in the culture fluid was detected using V cholerae H218 as the indicator strain (6). Drug sensitivities were examined by determination of the minimum inhibitory concentrations of polymyxin-B, erythromycin and tetracycline.…”
Section: Methodsmentioning
confidence: 99%